Optical coding of fusion genes using multicolor quantum dots for prostate cancer diagnosis - Lee, Hyojin; Kim, Chloe; Lee, Dongjin; Park, Jea Ho; Searson, Peter C.; Lee, Kwan Hyi (DOVE MEDICAL PRESS LTD, 2017)
Recent studies have found that prostate cancer expresses abnormal genetic markers including multiple types of TMPRSS2-ERG fusion genes. The expression level of different TMPRSS2-ERG fusion genes is correlated to pathologic variables of aggressive prostate cancer and disease progression. State-of-the-art methods for detection of TMPRSS2-ERG fusion genes include reverse transcription polymerase chain reaction (RT-PCR) with a detection limit of 1 fmol at urinary condition. RT-PCR is time consuming, costly, and inapplicable for multiplexing. Ability to identify multiple fusion genes in a single sample has become important for diagnostic and clinical purposes. There is a need for a sensitive diagnostic test to detect multiple TMPRSS2-ERG fusion genes for an early diagnosis and prognosis of prostate cancer. Here, we propose to develop an assay for prostate cancer diagnosis using oligonucleotide-functionalized quantum dot and magnetic microparticle for optical detection of rearranged TMPRSS2-ERG fusion genes at a low concentration in urine. We found that our assay was able to identify three different types of fusion gene with a wide detection range and detection limit of 1 fmol (almost the same level of the RT-PCR result reported). Here, we show detection of multiple TMPRSS2-ERG fusion genes using color-coded oligonucleotides in cell lysate and urine.
Keywords: MOLECULAR CHARACTERIZATION; CHEMISTRY